ANALISIS KEPUASAN NASABAH, KEPERCAYAAN NASABAH DAN CITRA MEREK TERHADAP LOYALITAS NASABAH PADA PT. BCA SYARIAH CABANG SURABAYA - Eryana Setyarti; Juliani Pudjowati; Elly Yuniar Nitawati (Jurnal Ekonomi dan Bisnis, 2026)
Competition in the banking sector in Indonesia is getting tighter nowadays. PT. BCA Syariah is a rapidly growing Islamic bank and has continued to grow over the past 10 years. Therefore, PT. BCA Syariah is committed to providing the best service and providing quality service products to build customer loyalty. The results of the study indicate that customer satisfaction has a significant positive effect on customer loyalty. Customer satisfaction has a significant positive effect on customer loyalty. Brand image has a significant positive effect on customer loyalty. Brand image has a significant positive effect on customer loyalty through customer trust. Thus, PT. BCA Syariah needs to improve customer satisfaction, brand image and customer trust because it can be a competitive advantage for the Company to create loyalty, and loyalty can increase profitability.